A computerized training platform for carrying out and testing experiments for electronics and electronic circuits labs for students of technical institutes (Journal of the College of Basic Education, 2023)
In this work, a computerized training platform was designed and tested to simulate a number of experiments in the electronics laboratory and the electronic circuits laboratory for students of technical institutes in order to provide an environment for training and retraining on those experiments outside the laboratory in facing the problem of the increase in the number of students in the laboratory class against the lack of sufficient number of devices. and training equipment. The platform included a ready-made simulation program produced by the American National Instruments Company, which was employed by the students to implement the linking of a number of laboratory test circuits. The researcher prepared two guides for the students to help them work on the platform, one of which was devoted to training the student to operate the simulation program and implement a number of exercises in order to gain practice on it, while the other guide included a presentation of (10) laboratory experiments that simulate the experiments that take place in the two mentioned laboratories in full, except that It is implemented through the training platform without the need for laboratory equipment. The platform was tested on (12) male and female students and their opinions were surveyed, in addition to presenting the platform to five expert teachers in the field of electronics and educational technology. As a result of the evaluation, the researcher concluded that the platform achieved a high degree of efficiency and effectiveness in training and retraining students to implement laboratory experiments, and that the simulation program has benefited in providing a useful training environment for students. Also, the presence of the computer platform was an incentive for the examined students to self-learning (outside the laboratory). ) to re-implement laboratory experiments by simulating them with a computer.